Teknologi Artisan Coffee Roasting Pada Pengusaha Café Probolinggo Dalam Upaya Menghasilkan Kopi Lokal Berkualitas - Alief Muhammad; Dani Hari Tunggal Prasetiyo; Hartawan Abdillah; Mas Ahmad Baihaqi; Hermanto; Ahmad Iskandar Rahmansyah (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2023)
The potential of the coffee industry in Probolinggo City, especially in the Micro, Small, and Medium-sized Enterprises food and beverage sector, including coffee shops, shows promising growth. For example, the coffee shops in the Tisnonegaran Village have become a significant tourist destination contributing to the local economy. However, coffee industry stakeholders face several challenges. The availability of high-quality coffee beans is a major concern as they often need to be sourced from outside the city, leading to stock instability and price fluctuations due to high delivery costs. To address these challenges, artisan coffee roasting technology training plays a crucial role. This training provides a deep understanding of the coffee bean roasting process, enabling coffee business owners to produce high-quality beans with unique flavor profiles. Knowledge about coffee bean selection, temperature control, and roasting times equips participants with the ability to optimize their coffee products. Furthermore, a plan for the development of artisan nano coffee roaster machine technology is also proposed to enhance the quality of mature coffee beans. Through collaboration with students, this technology's design is expected to bring innovation and a deeper understanding of effective roasting equipment and techniques. By combining training, technological development, and collaboration among coffee industry stakeholders, students, and the government, Probolinggo City has the potential to become a high-quality and competitive hub for the coffee industry in Indonesia.